A benchmark survey on the cyanide and protein content in the leaves and roots of cassava (Manihot esculenta crantz) in Iloilo. - Bacolod, Hanny Joy Catayas
The study is to establish a benchmark survey on the cyanide and protein content in the leaves and roots of cassava grown in selected sources in Iloilo.